Cryptography Application on RGB Overlapping Block Based PVD Using AES - Elhanafi, Andi Marwan; Tommy, Tommy; Siregar, Rosyidah; Yeni, Manovri; An-Nissa, Shahira (Sinkron : jurnal dan penelitian teknik informatika, 2022)
Pixel Value Differencing is a data hiding method in digital images that uses the difference in pixel values as a reference for inserting secret data bits. RGB Overlapping Block Based PVD is an optimization of PVD steganography. RGB Overlapping Block Based PVD provides a much larger capacity with acceptable quality. In this study, the AES cryptography application is used as an additional layer on RGB Overlapping Block Based PVD to provide additional security. Testing and observations have been carried out on the capacity and quality aspects of the embedding results using additional AES encryption. Based on the results, AES cryptography applications can be implemented properly where there is no significant change in terms of capacity and quality to the default RGB Overlapping Block Based PVD.